1903 Haw. Sess. Laws 55 - (:unkn) unknown (My University, 1903)
Ch. 8, § 25: Granted the Board of Supervisors of each county the jurisdiction and power to adopt rules and regulations for the keeping and storing of powder, Hercules powder, giant powder, kerosene, coal oil, benzoin, naptha, or other explosive or combustible materials.
Keywords: GUNPOWDER - STORAGE